FRI0261 Assessment of autophage function in systemic lupus erythematosus in respect of hyperlipidemia and immunosuppressive drugs. (12th June 2018) - Hamada, A.S.; aref, M.I.; salahdin, W.A.
Abstract : Background: Autophagy is an orchestrated homeostatic process to eliminate unwanted proteins and damaged organelles. Lipid turnover, as well, is controlled by autophagy through a process described as lipophagy. Defective lipophagy has been already linked to important metabolic disorders such as fatty liver, obesity and atherosclerosis. Objectives: Assessment of autophagy focusing on lipids regulation in untreated newly diagnosed systemic lupus Erythematosus (SLE) patients and after three months of treatment with immunosuppressive drugs. Methods: Subjects in this study have been divided into three groups. Group 1 included 60 newly diagnosed SLE patients before receiving any treatment, group2 included the same subjects of group 1 after three months of treatment with immunosuppressive drugs and group 3 included 30 healthy donors of matched age and sex as a control group. For each subject, disease activity was assessed by (SLEDAI) score, lipid profile was measured in addition to evaluation of lipids uptake, enhanced phagocytosis and intracellular killing ability of monocytes and neutrophils using Sudan Black B stain and Nitroblue tetrazolium stain mixed with latex particles coated with antibodies. Microscopic pictures were captured and quantified by ImageJ. Results: 95% of patients were females(57/60) with mean of age(39.7±8.6). Mean of SLEDAI score in group 1 was (18.6±3.4) decreased in group 2 (3 months after treatment) to (10.4±4.2). There was a positive correlation between total cholesterol, LDL and triglycerides and disease activity(SLEDAI score) (r=0.677, r=0.603 and r=0.718; respectively). On the contrary, There was a negative correlation between HDL and disease activity(r=−0.396). Furthermore, there was a negative correlation between lipid content of cells and intracellular killing and disease activity(r=−0.258 and r= −0.324; respectively). After 3 months, 100% of patients were taking Corticosteroids and Hydroxychloroquine(60/60).18.3% of patients received Azathioprine(11/60), 40.0% received Cyclophosphamide(24/60) and 15% received Mycophenolate(9/60) besides Corticosteroids and Hydroxychloroquine. Comparing group 2 to group 1, there was significant increase in cholesterol, LDL and trigycerides (p=0.027, p=0.021 and p=0.017; respectively) while HDL showed insignificant difference(p=0.0740). Lipid content in cells and intracellular killing significantly decreased(p=0.0322 and p=0.0271; respectively). Conclusions: Autophagy is deficient in patients with SLE aggravated by immunosuppressive drugs so they are more susceptible to infections and dyslipidemia. Consequently, lipid lowering drugs are definitely required to decrease comorbidity. Disclosure of Interest: None declared